2020
DOI: 10.1007/s11695-020-04874-w
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in Unmet Need for Metabolic Surgery in England: a Retrospective, Multicohort Analysis

Abstract: Metabolic surgery provision is severely limited despite extensive supportive trial evidence. This study estimated the eligible population and the unmet need for metabolic surgery within English regions. Health Survey for England, National Diabetes Audit and population estimates were used to estimate the metabolic surgery eligible population by English region. Hospital Episode Statistics data was examined for metabolic surgery procedure volume by region (2013-2019). Regression analysis examined factors associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…People living with obesity have been shown to have higher intensive care admissions and mortality during the recent coronavirus pandemic [ 10 , 11 ] which has brought focus to the delivery of metabolic surgical services [ 12 , 13 ]. However, studies demonstrate only a small proportion of the eligible population receive surgical intervention for obesity-related metabolic disease [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…People living with obesity have been shown to have higher intensive care admissions and mortality during the recent coronavirus pandemic [ 10 , 11 ] which has brought focus to the delivery of metabolic surgical services [ 12 , 13 ]. However, studies demonstrate only a small proportion of the eligible population receive surgical intervention for obesity-related metabolic disease [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…32 Whilst surgical risk following bariatric-metabolic surgery is reported as a concern by non-obesity clinicians, 33 the mortality rate following bariatric-metabolic surgery is lower than cholecystectomy, 34 which is one of the most commonly performed abdominal operations in the NHS. 35 Studies previously performed in the UK indicate variation in both regional bariatric-metabolic surgery provision 36 and in commissioning criteria 37 which in some cases did not follow NICE guidance, which may explain the limited delivery in the NHS.…”
Section: Associations With the Type Of Bariatric-metabolic Surgery Pr...mentioning
confidence: 99%
“…Prior research using routinely collected datasets has demonstrated that only 0.2% (6500 operations/year) of eligible English patients receive NHS-funded bariatricmetabolic surgery. 36,47 This compares with over 50,000 bariatric-metabolic surgical operations annually in France 47,48 reasons for the severely limited treatment intensification for people with severe obesity and T2DM in the NHS.…”
Section: Associations With the Type Of Bariatric-metabolic Surgery Pr...mentioning
confidence: 99%
“…Currently, the most effective therapy to treat obesity in the long term consists of bariatric surgery, which has seen a massive increase in the last few years [2]. Despite this, only a small proportion of eligible obese patients (approximately 0.25 %) undergo bariatric surgery [3].…”
Section: Introductionmentioning
confidence: 99%